Experience of Using Rituximab in a Girl with Severe Systemic Lupus Erythematosus - A. A. Lebedenko; A. M. Sarychev; A. V. Kharlamova; E. V. Nosova; E. A. Tarasova; K. V. Grin'ko (Union of pediatricians of Russia, 2015)
Heavy complications of systemic lupus erythematosus, such as the anti-phospholipin syndrome, generalized vaskulit and severe defeats of the central nervous system continue to remain relevant. There is a frequent development of side effects against high-dose therapy by glucocorticosteroids and cytostatics. In this regard the development of new methods of pathogenetic therapy, selectively influencing the segments of its pathogenesis, is vitally important. The article features a heavy case of systematic lupus erythematosus with central nervous affection where clinical and laboratory activity led up to the development of complications during the usage of the standard therapy schemes. The rapid and significant effectiveness of Rituximab in a complex treatment of heavy forms of systemic lupus erythematosus was demonstrated.